Operating surplus in financial management of Polish local government units - Błażuk, Katarzyna (Management and Administration Journal, 2019)
The aim of the article is to assess the currently effective limiting mechanisms for debt incurrence capability of Polish local government units (LGU), which is based on the size of the generated operating surplus. Moreover, the article includes a verification of a hypothesis stating that from 2011, the level of operating surplus significantly influences the investment decisions of LGUs. The article also skeptically scrutinizes the introduction of the operating surplus generation imperative with reference to the LGU subsector (a legal ban of deficit in the current part for LGUs) without similar restrictions regarding the central subsector, which was responsible for about 93% of total public debt in 2001-2016. The methodology applied includes statistical data analysis, as well as a dogmatic-legal method. The dependence of debt incurrence capability on generated operating surplus is to be positively appraised – the financial ratio which incorporates the size of the surplus is an indicator that defines a safe level of debt and therefore accurately reflects the financial condition and credit capabilities of LGUs. This value determines, not only the formal, but also the real credit capability of the unit. The reform of the LGU finance system without any additional constraints on the central level will not lead to the general rejuvenation of the public finance.